2016
DOI: 10.1016/j.tips.2016.01.005
|View full text |Cite
|
Sign up to set email alerts
|

APP Receptor? To Be or Not To Be

Abstract: Amyloid Precursor Protein (APP) and its metabolites play a critical role in Alzheimer’s disease pathogenesis. The idea that APP may function as a receptor has gained momentum based on its structural similarities to type I transmembrane receptors, and the identification of putative APP ligands. Here we review the recent experimental evidence in support of this notion and discuss how this concept is viewed in the field. Specifically, we focus on the structural and functional characteristics of APP as a cell surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
112
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(114 citation statements)
references
References 253 publications
(410 reference statements)
2
112
0
Order By: Relevance
“…One candidate is APP itself which has many known neuronal ligands [69] including APP, which is more highly expressed on neurons than on glial cells [70,71].…”
Section: Discussionmentioning
confidence: 99%
“…One candidate is APP itself which has many known neuronal ligands [69] including APP, which is more highly expressed on neurons than on glial cells [70,71].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, modulation of the APP-Gαo pathway by either physiologic or pathological factors might continue to regulate the motile responses of neurons throughout life 7,67 . Moreover, given suggestive evidence that the misregulation of normal APP signaling can induce neurodegenerative responses (as noted above), we speculate that chronic activation of Gαo-dependent targets (including Ca 2+ channels and stress/survival kinases) might also perturb synaptic remodeling and provoke neuronal dystrophy, thereby contributing to brain atrophy.…”
Section: Amyloid Precursor Protein and The Control Of Neuronal Migrationmentioning
confidence: 76%
“…Although many intracellular proteins can interact with APP under certain conditions, 7 considerable evidence has shown that holo-APP directly binds and regulates the heterotrimeric G protein Go, 24-26 suggesting that APP functions as an unconventional G protein-coupled receptor (GPCR). Whereas canonical GPCRs assume a heptahelical configuration, several type-1 (single pass) receptors also regulate heterotrimeric G protein signaling 27 .…”
Section: Amyloid Precursor Protein and The Control Of Neuronal Migrationmentioning
confidence: 99%
“…Synapse formation and maintenance involves homo- and heterotypic interactions of Synaptic Cell Adhesion Molecules (SAM), including APP/APLP (Siddiqui and Craig, 2011), extracellular matrix components, extracellular ligands such as soluble APP fragments and other growth factors, as well as their adjacent receptors (Deyts et al, 2016). Herein, we present the signaling pathways involved in synapse formation, synaptic plasticity and synaptic neurotransmission in which APP-binding proteins participate, with a particular focus on the signaling events in which APP intracellular YENPTY domain binding proteins may play a role to alter synaptic function.…”
Section: App/aplp Binding Proteins and Synaptic Functionmentioning
confidence: 99%